Interpreting results from using bio-economic modeling for global and regional ex ante impact assessment - Creamer, Bernardo; Enahoro, Dolapo; Kleinwechter, Ulrich; Gbegbelegbe, Sika; Hareau, Guy; Swamikannu, Nedumaran; Nelgen, Signe; Telleria, Roberto; Wiebe, Keith D. (International Association of Agricultural Economists, 2015)
Creamer, Bernado; Enahoro, Dolapo; Kleinwechter, Ulrich; Gbegbelegbe, Sika; Hareau, Guy; Swamikannu, Nedumaran; Nelgen, Signe; Telleria, Roberto; Wiebe, Keith